PENGARUH FASILITAS TERHADAP REVISIT INTENTION DENGAN KEPUASAN TAMU SEBAGAI VARIABEL INTERVENING (STUDI KASUS: NOVOTEL JAKARTA GAJAH MADA) - Kurniawan, Richard; Hanifah, Regina Dewi (ULTIMA Management, 2023)
Abstract- This research is motivated by 168 complaints from the Trust You website, regarding the facilities at Novotel Jakarta Gajah Mada that affect the level of revisit intention below the target. This study aimed to determine the influence of the independent variable facility on the dependent variable of revisit intention through guest satisfaction as an intervening variable. The type of research used is the descriptive quantitative method. The sampling method in this study used the Purposive Sampling technique. The research population is Novotel Jakarta Gajah Mada guests in one year, totaling 66,537. The sample used in this study was 100 respondents who had visited and used the facilities in Novotel Jakarta Gajah Mada, which were obtained using the Slovin formula. The data were collected from a Google Forms questionnaire where respondents used a Likert Scale to assess agreement with each question. The data was processed using the SmartPLS 4 data analysis software. The results showed that facilities had a positive and significant effect on guest satisfaction and revisit intention, while guest satisfaction had a positive and significant influence on revisit intention at Novotel Jakarta Gajah Mada. The better facilities at Novotel Jakarta Gajah Mada will increase guest satisfaction and revisit intention. Keywords: Facilities; Guest Satisfaction; Revisit Intention; Hotel